Distributional Gains of Near Higher Earners - Charles M. Beach (Queen's University, Department of Economics, 2018)
This paper looks at changes in employment and relative wages of near higher earnings (NHE) workers between middle-class (MC) and higher earners (HE) in Canada over 2000-2015. An approach is also forwarded for evaluating these changes in terms of underlying demand and supply factors. It is found that the NHE behaves as a transition group between quite different patterns of change of the MC and HE groups, and that these changes have been recently attenuating. The MC group experienced a downward shift in employment demand, the HE group an upward shift in demand, and the NHE group an upward shift in supply of workers.
Keywords: C12; J20; J31; 330; Income equality; Canadian earnings; near higher earnings